A multi-directional vibration isolator based on Quasi-Zero-Stiffness structure and time-delayed active control. (September 2015) - Xu, Jian; Sun, Xiuting
Abstract: The potential beneficial performance of a Multi-Direction Quasi-Zero-Stiffness vibration isolator (MDQZS-VI) with linear time-delayed active control is investigated in this study. From the analysis of vibration property such as natural frequency, it is found that the isolation effectiveness of the MDQZS-VI for different directions can be adjusted respectively. The vertical direction natural frequency and damping property of the MDQZS-VI are dependent on structural parameters while the horizontal direction natural frequency and damping coefficient are related to the active control parameters. Moreover, bifurcation analysis shows that the values of control strength and time-delay have effect on the stability of horizontal vibration. By solving the displacement transmissibility for multi-direction, it is shown that structural parameters and active control coefficients could be designed deliberately so that natural frequencies are reduced and nonlinear damping coefficients are increased which is helpful for vibration suppression. The results provide a useful insight into the analysis and design of multi-direction QZS vibration isolator by exploiting potential nonlinear benefits of the time delay in vibration active control. Highlights: Utilizing time delay as adjustable parameter in active control. Reforming Quasi-Zero-Stiffness system from one-direction isolation to multi-direction isolation. Time delay and structural parameters improve multi-direction isolation effectiveness for different excitations. Nonlinearity has help for vibration isolation in high frequency range.